1956
DOI: 10.1152/ajplegacy.1956.184.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Lactic Acid in the Intact Rabbit

Abstract: The metabolism of the lactic acid was studied in normal intact rabbits making use of C14 labeled l (+) lactate. The circulating lactate is being used up and renewed at a rapid rate. The turnover time is about 30 minutes. Eighty to ninety per cent of the lactate is disposed of by direct oxidation. Only a small percentage can be accounted for as glucose, glycogen and by the oxidation of these. Lactate that is produced in emergency states can serve as a quick fuel for vital tissues in these situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The dose level in this study was approximately more than 100 times higher than EFFECT AND FATE OF LACTIC ACID 127 the expected intake in humans from lactic acid drinks. Drury and Wick (18) reported that in the constant injection method, 65% of the dosed lactic acid was degraded to expired CO2 in rabbits. In our experiments, 61.3 and 42.4% of the dosed lactic acid in the control and the experimental group were degraded to expired CO2 for 6 hr.…”
Section: Discussionmentioning
confidence: 99%
“…The dose level in this study was approximately more than 100 times higher than EFFECT AND FATE OF LACTIC ACID 127 the expected intake in humans from lactic acid drinks. Drury and Wick (18) reported that in the constant injection method, 65% of the dosed lactic acid was degraded to expired CO2 in rabbits. In our experiments, 61.3 and 42.4% of the dosed lactic acid in the control and the experimental group were degraded to expired CO2 for 6 hr.…”
Section: Discussionmentioning
confidence: 99%
“…A carotid artery was exposed and cannulated (PE 190 (Dobson and Phillipson, 1956;Bensadoun et al, 1962;Sellers, 1965), dogs (Kvietys and Granger, 1981), and rats (Demigné and Rémésy, 1985) (Vernay, 1987b) or butyrate (Vernay, 1987c propionate (Vernay, 1987b) or butyrate (Vernay, 1987c (Clauss and Hornicke, 1979a,b; and corticosterone (Bonnafous and Raynaud, 1968;Kawakami et aL, 1972) are doubled, it appears that the absorptive processes Vernay, 1987a,d) (Roediger, 1980;Roediger and Moore, 1981;Cummings, 1984), rat (Roediger, 1982) (Aikawa et al, 1972;Felig, 1973). The presence of an acetyl-CoA synthetase mainly located in the cytosol fraction (Woodnutt and Parker, 1978) indicates that in rabbit liver, as in rat liver (Hanson and Ballard, 1967;Knowles et al, 1974;Scholte and Groot, 1975 (Beauville et al, 1974;McMillan et al, 1975;Bonnafous and Raynaud, 1978;Vernay, 1987a (Drury and Wick, 1956;Vezinhet and Nougu b .., 1977;Jones andParker, 1977, 1981 ).…”
Section: Methodsmentioning
confidence: 99%
“…Putnam (1979b) Although the experiments presented here do not include biochemical assays to determine the nature of the molecules that the labelled carbon is incorporated into, it is likely that a significant portion is in glycogen. Previous studies of mammalian systems have indicated that a large percentage of endogenous lactate is converted to glycogen (Hermansen and Vaage, 1977;McLane and Holloszy, 1979 , 1942) to 80-90\ expired in rabbits (Drury and Wick, 1956). Bendall and Taylor (1970) There has been very little data concerning the fate of lactate, especially in amphibians.…”
Section: Oxygen Consumption Rates and Lactate Concentrations During Rmentioning
confidence: 99%
“…Recent studies concerning the fate of lactic acid after activity, essentially all on manunals (Drury and Wick, 1956;Brooks! !_ al., 1973;Issekutz et al, 1976;Hermansen and vaage, 1977;McLane and Holloszy, 1979;Brooks and Gaesser, 1980) have led to the conclusion that the Cori cycle cannot account for either lactate disappearance or glycogen synthesis and suggest that lactate is either mainly converted to glycogen in the muscle itself (Hermansen and vaage, 1977;McLane and Holloszy, 1979) or mainly oxidized to co 2 (Brooks and Gaesser, 1980;Drury and Wick, 1956).…”
Section: Introductionmentioning
confidence: 99%